Reduced neuroplasticity in aged rats: a role for the neurotrophin brain-derived neurotrophic factor - Calabrese, Francesca; Guidotti, Gianluigi; Racagni, Giorgio; Riva, Marco A. (Neurobiology of aging, 2013)
Aging is a physiological process characterized by a significant reduction of neuronal plasticity that might contribute to the functional defects observed in old subjects. Even if the neurobiological mechanisms that contribute to such impairment remain largely unknown, a role for neurotrophic molecules, such as the neurotrophin brain-derived neurotrophic factor (BDNF), has been postulated. On this basis, the purpose of this study was to provide a detailed investigation of the BDNF system, at transcriptional and translational levels, in the ventral and dorsal hippocampus and in the prefrontal cortex of middle-aged and old rats, compared with in adult animals. The expression of major players in BDNF regulation and response, including the transcription factors, calcium-responsive transcription factor, cyclic adenosine monophosphate (cAMP) responsive element-binding protein (CREB), and neuronal Per Arnt Sim (PAS) domain protein 4, and the high-affinity receptor tropomyosin receptor kinase B (TrkB), was also analyzed. Our results demonstrate that the BDNF system is affected at different levels in aged rats with global impairment including reduced transcription, impaired protein synthesis and processing, and decreased activation of the TrkB receptors. These modifications might contribute to the cognitive deficits associated with aging and suggest that pharmacological strategies aimed at restoring reduced neurotrophism might be useful to counteract age-related cognitive decline.